Variability of surface water hydrochemical characteristics in the Shokalsky strait based on the results of observations at the “Cape Baranov Ice Base” in 2018–2019 - N. I. Savelieva; E. D. Dobrotina; S. B. Kuzmin; A. Yu. Ipatov; A. B. Goncharova; A. P. Nedashkovsky; Н. И. Савельева; Е. Д. Добротина; С. Б. Кузьмин; А. Ю. Ипатов; А. Б. Гончарова; А. П. Недашковский (BRICS Law Journal, 2021)
In connection with the progressing climate change in the Arctic, it is extremely important to conduct systematic long-term monitoring in the high-latitude Arctic. An important place in the network of monitoring stations is occupied by the research Station «Cape Baranov» Ice base», located on Severnaya Zemlya (in the area of the Shokalsky Strait). The article presents the results of hydrochemical observations at the Ice base from December 02, 2018 to July 15, 2019. 35 hydrochemical stations were operated from the ice of the strait in the seawater layer of 0–110 m. A significant temporal variability of the characteristics in the upper layer (0–10 m) has been recorded. Four phases of variability of the hydrochemical parameters (HP) have been identified. In December (phase 1) the HP values indicate the presence of surface waters, the origin of which we associate with the transformed river waters (TRW) of the Ob and Yenisei, coming from the Kara Sea. From January to mid-April (phase 2) the highest salinity levels and homogeneous HP are observed due to intensive vertical mixing of waters in the autumn-winter period. At the end of April — May (phase 3) there is a slight desalination of the surface layer in the Shokalsky Strait, with HP pointing to the presence of TRW. From June to July, 15 (4th phase), there is a sharp decrease in the salinity, an increase in oxygen and pH, as well as a drop in the concentration of all the biogenic elements. Such HPs indicate both additional desalination from ice and snow melting and the beginning of phytoplankton bloom. An estimation has been carried out of the proportion of TRW and waters formed during sea ice melting. The average integral proportion of TRW in the water column is ~ 4 %, and for melt water this indicator is close to zero. The influence of ice formation on the hydrochemical characteristics of the surface layers is most noticeable in the 1st and 3rd phases. During the period of strong desalination of the surface waters (May —July), the TRW proportion can reach 10 % or ...